Sebaceous carcinoma of scalp with proliferating trichilemmal cyst - Siddhi Chikhalkar; Gaurav Garg; Rameshwar Gutte; Uday Khopkar (Wolters Kluwer Medknow Publications, 2012)
Sebaceous carcinoma is a rare neoplasm of the sebaceous gland. It is diagnosed mainly on histopathology and, clinically, it may mimic other neoplasms like squamous or basal cell carcinoma. We came across a patient presenting with a non-healing ulcer over the left temporo-parietal region of the scalp since 4 years and a single asymptomatic nodule over the occipital region since 3 years. Histopathology from an ulcer was pathognomonic of sebaceous carcinoma and that from a nodule was suggestive of proliferating trichilemmal cyst. The patient was screened for Muir Torre syndrome. We referred the patient to the oncologist for further management, where the patient was advised complete excision of the lesion.